Evaluasi Penggunaan Obat Antidiabetik Pada Pasien Dengan Diabetes Melitus Tipe 2 Rawat Jalan Di Rumah Sakit Efarina Kota Periode April - Juni Tahun 2024. - Marbun, Lilis Oktavia; Sumule, Arsiyati; Marbun , Meyana; Sipayung, Hekdin (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
Diabetes Mellitus (DM) is a condition that is becoming more common throughout the world. Up to 346 million people worldwide have diabetes, and estimates suggest that this number will increase to 380 million by 2025 (WHO, 2011). The aim of this study is to evaluate the use of antidiabetic drugs in outpatients with type 2 diabetes mellitus at Efarina Hospital, Pematangsiantar City for the period April-June 2024. This research uses retrospective data collection, namely collecting past data through medical record sheets from diabetes sufferers. Mellitus Type 2 at the Efarina Etaham Hospital, Pematangsiantar City for the period April-June 2024. The data taken is in the form of prescription records from patients who diagnosed Diabetes. Data processing is carried out with a descriptive plan, namely a study that aims to describe the events found. This research involved 83 patients using Type 2 Diabetes Mellitus medication. Based on the results of research conducted at the Efarina Etaham Hospital, Pematangsiantar City, it can be concluded that the most widely used oral anti-diabetic medication in the April-June 2024 period was Glimepiride in 60 patients (65, 21%), Metformin in 49 patients (49%), Gliquidone in 17 patients (18.47%). Keywords : Evaluation; Diabetes mellitus; Antidiabetic; Hospita l